Recent advances in fish and wildlife ecology and biology - Kenvon, Dylan (New Delhi Random Exports, 2013)
"Most biological scientists need a Ph.D. degree in biology or one of its subfields to work in research or development positions. A period of postdoctoral work in the laboratory of a senior researcher has become common for biological scientists who intend to conduct research or teach at the university level. Those interested in studying the environment also should read this book and become familiar with applicable legislation and regulations. This book comprises the vast body of research on wildlife ecology and includes original research. The book provides diversified information regarding diversity of spider fauna, aquatic hemipterans, soil micro-arthropods, polychaetes, prawns and also the fish fauna on one hand besides focusing on molecular markers for the analysis of genetic biodiversity with special reference to Indian fish fauna. The book will be a landmark and shall hopefully be very useful for those workers and planners who are involved in the studies related to the diversified animals and also throw light on their present status in the context the threats and need for their future conservation."
Keywords: Animal ecology; Aquatic biology; Fishes -- Ecology